CRISPR‐induced exon skipping of β‐catenin reveals tumorigenic mutants driving distinct subtypes of liver cancer. Issue 4 (8th February 2023) - Mou, Haiwei; Eskiocak, Onur; Özler, Kadir A.; Gorman, Megan; Yue, Junjiayu; Jin, Ying; Wang, Zhikai; Gao, Ya; Janowitz, Tobias; Meyer, Hannah V.; Yu, Tianxiong; Wilkinson, John E; et al.
Abstract: CRISPR/Cas9‐driven cancer modeling studies are based on the disruption of tumor suppressor genes by small insertions or deletions (indels) that lead to frame‐shift mutations. In addition, CRISPR/Cas9 is widely used to define the significance of cancer oncogenes and genetic dependencies in loss‐of‐function studies. However, how CRISPR/Cas9 influences gain‐of‐function oncogenic mutations is elusive. Here, we demonstrate that single guide RNA targeting exon 3 of Ctnnb1 (encoding β‐catenin) results in exon skipping and generates gain‐of‐function isoforms in vivo . CRISPR/Cas9‐mediated exon skipping of Ctnnb1 induces liver tumor formation in synergy with YAP S127A in mice. We define two distinct exon skipping‐induced tumor subtypes with different histological and transcriptional features. Notably, ectopic expression of two exon‐skipped β‐catenin transcript isoforms together with YAP S127A phenocopies the two distinct subtypes of liver cancer. Moreover, we identify similar CTNNB1 exon‐skipping events in patients with hepatocellular carcinoma. Collectively, our findings advance our understanding of β‐catenin‐related tumorigenesis and reveal that CRISPR/Cas9 can be repurposed, in vivo, to study gain‐of‐function mutations of oncogenes in cancer. © 2023 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of The Pathological Society of Great Britain and Ireland.